SPE/IADC International Drilling Conference and Exhibition 2021
DOI: 10.2118/204098-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Medical-Inspired Framework to Classify Downhole Shocks Waveforms While Drilling

Abstract: This paper presents a medical approach to classify shock waveforms acquired at 31,250 hertz downhole. The shock signals are treated as drilling electrocardiogram (D-ECG). The D-ECGs are processed using clustering algorithms and merged with drilling incidents to identify an arrhythmic signature pattern that can lead to catastrophic failures. In medicine, the analysis of heartbeat cycles in an electrocardiogram signal is very important for monitoring heart patients. In the drilling industry, downh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…They use high-temperature batteries to supply power and independently collect and record downhole vibration signals for several months. Through in-depth analysis of the downhole vibration signals measured by these miniature vibration recorders, it can be found that the high-frequency measurement results of downhole vibration signals can record the dynamic response of downhole drilling tool assemblies in more detail, which is beneficial to the analysis of abnormal downhole vibrations and the diagnosis of drilling tool faults [15][16][17][18]. In 2016, Jeremy summarized the classification of downhole vibration and the corresponding frequency range and discussed the necessity and benefits of the high-frequency vibration measurement [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They use high-temperature batteries to supply power and independently collect and record downhole vibration signals for several months. Through in-depth analysis of the downhole vibration signals measured by these miniature vibration recorders, it can be found that the high-frequency measurement results of downhole vibration signals can record the dynamic response of downhole drilling tool assemblies in more detail, which is beneficial to the analysis of abnormal downhole vibrations and the diagnosis of drilling tool faults [15][16][17][18]. In 2016, Jeremy summarized the classification of downhole vibration and the corresponding frequency range and discussed the necessity and benefits of the high-frequency vibration measurement [17].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Matheus et al obtained the high-frequency measurement signal of vibration by using the offline downhole vibration measurement method with a sampling frequency of 31250 Hz and conducted the "ECG" diagnosis of the downhole vibration signal through the spectrum diagram of the high-frequency measurement data. It was found that these high-frequency data (300 times the frequency of the standard measurement signal) can record more specific details about the dynamic response of the drilling tool, which is beneficial for analyzing and diagnosing abnormal vibration in the well [18]. In 2023, Srivastava et al discussed sampling frequency of measurements greatly impacts the detection of downhole vibrations.…”
Section: Introductionmentioning
confidence: 99%